Pengaruh Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) disertai Numbered Heads Together (NHT) Terhadap Pemahaman Konsep Matematis Siswa Kelas VIII SMPN 3 Palembayan Kabupaten Agam - Putra, Ariska; Aima, Zulfitri; Haryono, Yulia (Pendidikan Matematika, 2013)
The research was due to the lack of studentâs ability in comprehension mathematic concept. Morever, the students seemed to have ineffective discussion within the group during the learning process that their mathematicsâ result were low. The research aimed at finding out whether studentsâ mathematic comprehension which were taught using Student Team Achievement Division with Numbered Heads Together better than that of conventional learning. The design of the research was experimental research. The population was student of grade VIII SMPN 3 Palembayan. Based on the result of random sampling technique, grade VIII3 was chosen as the experimental group, while the grade VIII4 as the control group. The instrument used was an essay test. Based on the data analysis, it was obtained that both class were distributed homogeny and normal. Based on the analysis of hypotesis, it was obtained that the p-value = 0.003 was < Â Â = 0,05. Thus, the hypotesis was accepted. Therefore, it can be concluded that studentsâ math consept comprehension using Cooperative Learning Model Student Team Achievement Division with Numbered Heads Together was better than that of conventional technique with the 95% degree of certainty